The Contribution of Self-Esteem and Parenting towards Aggressive Behavior of Child Victims’ Domestic Violence - Opi Andriani; Alizamar Alizamar; Yeni Karneli (International Journal of Research in Counseling and Education, 2020)
Children who live in violent environments have aggressive tendencies as a result of the interaction process. Aggressive behavior of children is influenced by several factors such as improper care, stress, low self-esteem, bad relationships and the display of violence in the mass media. This research aims at examining the contribution of self-esteem and parenting to the aggressive behavior of child victims of domestic violence. The research used a quantitative approach with a descriptive and correlation type. The research respondents  were the students of SMA Negeri Padang who were identified as 73 victims of domestic violence victims, selected by using a purposive sampling technique. The data were collected using the CFSEI-2 inventory for self-esteem and Likert model scale for aggressive behavior with a reliability level of 0.899 and 0.915 for parenting. The data processing used a multiple regression analysis technique with the help of SPSS for Windows Release 20. The findings of this research indicated that self-esteem and parenting together contributed to the aggressive behavior of child victims of domestic violence by 41.7%.